The corticosteroids in aesthetics - Chrysoglou, Charikleia-Lydia; Goula, Maria (Health & Research Journal, 2018)
The aim of this study is to present the role of corticosteroids in aesthetics. To begin with, the actions of corticosteroids are analyzed as well as their adverse effects, their classification and methods to avoid possible adverse effects when they are used topically. The use of corticosteroids in aesthetics is limited because of their variety of pharmacological actions. Corticosteroids affect almost every system of human body even if they are used topically, so they must not be considered as moisturizing or soothing products, but as medications with specific properties, indications and contraindications. Their administration is always on medical prescription, at a certain dose and for a specific period of time, even for local application on the skin. In addition, the classification of topical corticosteroids according to their potency by World Health Organization (WHO) is further discussed. Furthermore, the role of topical corticosteroids is further investigated. Finally, methods of application depending on the skin area are analyzed and combinations of corticosteroids with other medications such